Impact of Chronic Kidney Disease on Survival After Amputation in Individuals With Diabetes - Lavery, Lawrence A. (American Diabetes Association, 2010)
OBJECTIVE: To identify factors that influence survival after diabetes-related amputations. RESEARCH DESIGN AND METHODS: We abstracted medical records of 1,043 hospitalized subjects with diabetes and a lower-extremity amputation from 1 January to 31 December 1993 in six metropolitan statistical areas in south Texas. We identified mortality in the 10-year period after amputation from death certificate data. Diabetes was verified using World Health Organization criteria. Amputations were identified by ICD-9-CM codes 84.11–84.18 and categorized as foot, below-knee amputation, and above-knee amputation and verified by reviewing medical records. We evaluated three levels of renal function: chronic kidney disease (CKD), hemodialysis, and no renal disease. We defined CKD based on a glomerular filtration rate <60 ml/min and hemodialysis from Current Procedural Terminology (CPT) codes (90921, 90925, 90935, and 90937). We used χ(2) for trend and Cox regression analysis to evaluate risk factors for survival after amputation. RESULTS: Patients with CKD and dialysis had more below-knee amputations and above-knee amputations than patients with no renal disease (P < 0.01). Survival was significantly higher in patients with no renal impairment (P < 0.01). The Cox regression indicated a 290% increase in hazard for death for dialysis treatment (hazard ratio [HR] 3.9, 95% CI 3.07–5.0) and a 46% increase for CKD (HR 1.46, 95% CI 1.21–1.77). Subjects with an above-knee amputation had a 167% increase in hazard (HR 2.67, 95% CI 2.14–3.34), and below-knee amputation patients had a 67% increase in hazard for death. CONCLUSIONS: Survival after amputation is lower in diabetic patients with CKD, dialysis, and high-level amputations.